Chaos or complex systems? Identifying factors influencing the success of international and NESB graduate research students in Engineering and Information Technology fields. - Woodman, K.; Trevelyan, J.; Sahama, T.; Gudimetla, P.; Sharda, H.; Lucey, Anthony; Taji, A.; Narayanaswamy, Ramesh; Yarlagadda, P. (International Association of Technology, Education and Development (IATED), 2011)
The paper explores the results an on-going research project to identify factors influencing the success of international and non-English speaking background (NESB) gradúate students in the fields of Engineering and IT at three Australian universities: the Queensland University of Technology (QUT), the University of Western Australia (UWA), and Curtin University (CU). While the larger study explores the influence of factors from both sides of the supervision equation (e.g., students and supervisors), this paper focusses primarily on the results of an online survey involving 227 international and/or NESB graduate students in the areas of Engineering and IT at the three universities. The study reveals cross-cultural differences in perceptions of student and supervisor roles, as well as differences in the understanding of the requirements of graduate study within the Australian Higher Education context. We argue that in order to assist international and NESB research students to overcome such culturally embedded challenges, it is important to develop a model which recognizes the complex interactions of factors from both sides of the supervision relationship, in order to understand this cohort’s unique pedagogical needs and develop intercultural sensitivity within postgraduate research supervision.